INTEGRATED RISK MANAGEMENT IN HOSPITAL MANAGEMENT STRATEGY - Edi Kurnawan; Farida Yuliaty; Vip Paramarta; Kosasih (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
Risk management is a crucial aspect of hospital management to ensure the safety of patients, staff, and smooth operations. The implementation of integrated risk management helps hospitals identify, assess, and manage risks, both clinical and non-clinical, to minimize injuries, accidents, and financial losses. This article aims to analyze the importance of integrated risk management in hospital management strategies and identify challenges and solutions for its implementation. Based on a literature review and various case studies, it is found that the implementation of international standards such as ISO 31000 has successfully optimized risk management in hospitals, especially in dealing with operational and clinical risks. However, significant challenges are still encountered, such as the lack of professionals trained in risk management and limited supporting technology. Suggested solutions include intensive training for staff, implementation of a technology-based incident reporting system, and integrating risk management with financial processes to prevent budget discrepancies. With these measures, the hospital can increase the effectiveness of risk management, improve patient safety, and maintain optimal continuity of operations.